Improvisieren für mehr Beteiligung am Gottesdienst? - Schirr, Bertram J. (International journal of practical theology, 2019)
Analyzing contemporary experiments in homiletical and liturgical improvisation shows fresh and exciting potential for more participation in worship. The use of Free Jazz as a paradigm for liturgical and homiletical practice is complimented by the model of Theatrical Improvisation. By rendering empirical improvisations in liturgy and preaching as interactions, a grid of participatory improvisational strategies is generated that can be usefully employed for the analysis and improvement of other pastoral practices such as pastoral care or ministerial training.